Uzma Aslam Khan’ Trespassing: A Postcolonial Ecofeminist Analysis - Bashir, Saima; Yasmeen, Nimra (Pakistan Languages and Humanities Review, 2025)
The article examines Uzma Aslam Khan‘s Trespassing (2003) as a postcolonial text within the context of Vandana Shiva-influenced ecofeminism. Postcolonial ecofeminism is about environmental and gender inequities created by the legacy of colonialism and contemporary capitalism. The views of Vandana Shiva and Gayatri Spivak are combined here to understand how Trespassing addresses the difficulties faced by nature and women in the particular context of Pakistan. The qualitative method of research, close reading approach, ecofeminist and postcolonial literary theories are used to interpret the plot, characters, and symbolism of the narrative. By highlighting the ingenious knitting together of women‘s contributions to environmental challenges and power dynamics in postcolonial contexts, the study establishes what role literature can play in the fostering of a sustainable and just society. Hence a postcolonial ecofeminist point of view not only censures neocolonial practices but also attempts to inspire and embolden the resistance of the marginalized ones.